2012
DOI: 10.4111/kju.2012.53.8.547
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Periprostatic Nerve Block with and without Intraprostatic Nerve Block in Transrectal Ultrasound-Guided Prostatic Needle Biopsy

Abstract: PurposeControversy exists over the pain during prostate biopsy. Periprostatic nerve block is a commonly used anaesthetic technique during transrectal ultrasound (TRUS)-guided prostate biopsy. The recent trend toward increasing the number of cores has become popular. This practice further increases the need for a proper anaesthetic application. We compared the efficacy of periprostatic nerve block with or without intraprostatic nerve block.Materials and MethodsWe conducted a prospective double-blinded placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…For that reason, a good pain control is mandatory, especially in order to prevent patient's refusal to repeat biopsy. Some studies have showed that about 20% of patients who underwent biopsy would reject rebiopsy without any kind of analgesia (7). According to our results, the rate of tolerability in group 1 was about 73.2% and the rate of patient consent for repeating the procedure was about 34.1% in the same group.…”
Section: Discussionsupporting
confidence: 51%
“…For that reason, a good pain control is mandatory, especially in order to prevent patient's refusal to repeat biopsy. Some studies have showed that about 20% of patients who underwent biopsy would reject rebiopsy without any kind of analgesia (7). According to our results, the rate of tolerability in group 1 was about 73.2% and the rate of patient consent for repeating the procedure was about 34.1% in the same group.…”
Section: Discussionsupporting
confidence: 51%
“…1). After screening 46 RCTs15678910111213141516171819202122232425262728293031323334353637383940414243444546474849 met our study criteria and were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 6 31 Eight articles compared IRLA with no anesthesia or placebo gel; 6 13 six articles compared PPNB with no anesthesia; 7 , 11 , 14 17 three articles compared PPNB with periprostatic placebo injection; 10 , 14 , 18 six articles compared PPNB with IRLA; 7 , 10 , 11 , 19 , 21 nine articles compared combined PPNB and IRLA with PPNB alone; 21 29 and four articles compared combined PPNB and IPNB with PPNB alone. 15 , 17 , 30 , 31 For studies comparing PPNB with periprostatic placebo injection, an equivalent volume of normal saline was used. In all studies, biopsies were operated with an 18 G needle, and six to 14 core biopsies were performed for the participants.…”
Section: Resultsmentioning
confidence: 99%